Исследование деформаций и силовых параметров при холодной прокатке трехслойных пакетов "медь-алюминий-медь" - Загорянский, Владимир Георгиевич; Дикая, Луиза Эхматовна (НТУ "ХПИ", 2016)
В статье проведено сравнение полученных экспериментально толщин слоев после прокатки трехслойных пакетов "медь-алюминий-медь" и рассчитанных по предложенной ранее методике, включающей оптимизационную модель, основанную на энергетическом подходе. Сравнение показало, что полученные результаты практически совпадают, что подтверждает адекватность методики расчета. Экспериментально установлено, что уменьшение толщины слоя меди в исходном пакете приводит к снижению его деформации. Получены графики зависимостей среднего контактного давления на валки от соотношения толщин слоев в пакете. Снижение толщины слоя меди в исходном пакете приводит к уменьшению среднего контактного давления.

In the paper is compared the thickness of layers obtained experimentally after rolling of three-layered package "copper-aluminum-copper" and ones calculated in previously proposed method, that includes an optimization model based on the energy method. The comparison showed that the results are almost the same, which confirms the adequacy of the calculation method. It was established experimentally that the reduction in the thickness of the copper layer in the initial sandwich reduces its deformation. The obtained graphs of dependences of the average contact pres sure on the rolls on the ratio of the thicknesses of the layers in the sandwich (it was rolled as a two-layered packets, and three-layered sandwiches with cladding layers of a copper) show that this dependence is close to linear. It is established that the average contact pressure over the whole range of ratios of thicknesses of the layers in the sandwich from the side of the aluminum is higher than that of the copper. Reducing the thickness of the layer of copper in the origina l sandwich results in the reduction of the average contact pressure.
Investigation of deformations and force parameters at cold rolling three-layer packets "copper-aluminum-copper"
Keywords: холодная прокатка; трехслойный пакет; деформации слоев; оптимизационная модель; среднее контактное давление; cold rolling; three-layered package; deformations of layers; optimization model; average contact pressure